Kemanjuran Letrozole Dibandingkan dengan Clomiphene Citrate untuk Induksi Ovulasi pada Wanita dengan PCOS: Tinjauan Sistematis dan Analisis Meta - Pinda Hutajulu; Ronaldi Lawira (Lembaga Pengembangan Kinerja Dosen, 2026)
Polycystic ovary syndrome (PCOS) is the most common hormonal disorder in women of reproductive age and often causes ovulation disorders and infertility. For decades, clomiphene citrate (CC) was the go-to choice for stimulating ovulation, but letrozole is now considered a more effective alternative with the potential for better reproductive outcomes. This study systematically assessed the comparison of the effectiveness of letrozole and CC based on the PRISMA 2020 guidelines. Literature searches through PubMed and Google Scholar include randomized controlled clinical trials (RCTs) published between 2015–2025 in English, with a population of women diagnosed with PCOS. Data were combined using a fixed-effects model to calculate odds ratio (OR) and 95% confidence intervals, as well as assess heterogeneity through Cochran's Q and I² tests. Of the 11 RCTs involving 1,995 participants (1,000 using letrozole and 995 using CC), the rate of ovulation with letrozole ranged from 37.9–88%, while with CC it was 19.7–85.2%. Most studies showed significant improvements in ovulation and clinical pregnancy rates using letrozole (22–61%) compared to CC (13–43%). Overall, letrozole increased the chances of reproductive success (OR = 2.13; 95% CI = 1.73–2.61; p < 0.00001) with low heterogeneity, demonstrating better effectiveness and safety than CC.